Dificuldades e possibilidades de uma escola estadual de Rondonópolis em transformar-se em comunidade de aprendizagem - Silva, Elizabeth (2016)
The discussions raised in the research presented here refer to the dilemmas faced by school in today’s society, and the possibility of its transformation by means of the educative project called Learning Communities. This project has as objective the school social and cultural transformation, and was developed in the University of Barcelona by researchers of Especialized Center for Investigation of Practices to Overcoming Inequalities (CREA). In this research we highlight the process of implantation of Learning Communities (CdA) in a public school in Rondonópolis, a city in the State of Mato Grosso, Brazil, which we call as Public School Dreams Valley. Therefore, the aim of the research was to respond how the subjects of the school Dreams Valley understand the difficulties and possibilities of the school becoming a Learning Community. The objectives tried to analyze how subjects involved with educational successful performances understand the difficulties and possibilities of the school becoming a Learning Community; identify and analyze which elements could be transforming the educative practice from educational successful performances implemented at the school, in order to reach the improvement of learning; and identify from the perspective of an exprincipal, the current principal, a coordinator, teachers from the first and third cycles, a student and a volunteer the motives and actions which favor and are obstacles for such successful performances get extended, and the school become a Learning Community. The main authors referred to in the research when it comes to theoretical-methodological framework are: Habermas (2012) with communicative action theory, Freire (1967, 1984,1987, 1996, 1997 e 2013) referring to dialogic action theory, Flecha (1997) with the dialogic learning concept, and also theoretical elaborations of CREA about the educative proposal Learning Communities. We also refer to Mello, Braga e Gabassa (2012) about CdA in Brazil. It’s a qualitative research, with communicative methodological approach, which aims to promote the active participation of investigated groups, resulting in a major social impact, besides its scientific knowledge. The data collection relied on: communicative account, indepth interview, communicative observation and communicative discussion group. As research participants there were two teachers (one from the first cycle and another from the third cycle), management team (current principal and a coordinator, as well as the previous principal, who was present at the beginning of the project at the school), a student (an exstudent at the school, however she had active participation in the project), a volunteer of successful activities offered by the school, and six teachers from the final years which participated in the communicative discussion group. The data analysis was performed in an intersubjective manner, that is, after a preliminary analysis, with the elaboration of a feedback, we returned to the investigated subjects, in order to reach a consensus of interpretations. The analysis and the results indicate that even the transformation hasn’t been effective at the public school Dreams Valley many changes have happened. Among them, we can mention a relevant improvement in interpersonal relationships, learning improvement, increase in the extern index (IDEB) and a better participation of family members in meetings and also in some activities offered by the school. However, we highlight some exclusion elements, which present themselves as impeditive to the effective transformation of that school into Learning Communities: the support difficulty of managements in the conduction of works, the resistance of some teachers during the development of the project, and the lack of deepening in epistemological foundations of the Learning Communities proposal.